Development of Cadets Worksheets based on Problem Centered Learning as Applied Physics Learning Media - Nelfi Erlinda; Budi Rianto; Dody Efrianto (Kasuari: Physics Education Journal (KPEJ), 2018)
The purpose of this study to develop valid and practical Cadets Worksheets based on Problem Centered Learning. This type of research was a Research and Development (R & D) research, which uses six research steps: potential problems, information gathering, product design, design validation, design improvement, and testing. The research instrument used was a questionnaire of validity and questionnaire of practicability. Analysis techniques used to test the validity and practicality of learning materials developed student worksheet was Likert-scale analysis techniques. Based on validation data analysis by validator obtained average percentage value of Cadets Worksheet was 83,6% (very valid). The result of Cadets Worksheet practice percentage by students' was 83.4% (very practical). Based on the above data analysis can be concluded that Worksheet Physics based PCL developed valid and practical.